2023
DOI: 10.1111/corg.12523
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the right knots: The impact of board committee interlocks on the performance of Indian firms

Abstract: Research Question/IssueInformation processing, agency, and resource dependence perspectives provide diverging predictions regarding the relationship between board interlocks and firm performance, which are rooted in different perspectives on the roles of boards of directors. This study argues that these various approaches are reconcilable when considering the nature of board committees to which the interlocked directors are assigned.Research Findings/InsightsWe test our hypotheses on a sample of 5133 firm‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 161 publications
0
2
0
Order By: Relevance
“…Furthermore, the nomination committee must also utilize all its capabilities and the company's social environment to obtain quality board members. Edacherian et al (2024) found a link between the nomination and remuneration committees of companies in India, providing them with access to human resources and information regarding appropriate incentive structures that will improve performance. So based on the two theories above, we conclude that it is very important to study the nomination and remuneration committee to maximize the alignment of interests of the principal and agent and to have superior resources on the board to achieve company goals.…”
Section: Remunerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the nomination committee must also utilize all its capabilities and the company's social environment to obtain quality board members. Edacherian et al (2024) found a link between the nomination and remuneration committees of companies in India, providing them with access to human resources and information regarding appropriate incentive structures that will improve performance. So based on the two theories above, we conclude that it is very important to study the nomination and remuneration committee to maximize the alignment of interests of the principal and agent and to have superior resources on the board to achieve company goals.…”
Section: Remunerationmentioning
confidence: 99%
“…We have reviewed the literature on nomination and remuneration committees for relevant articles published in the last 26 years in the Scopus index, articles ranging from Conyon and Peck (1998) to Edacherian et al. (2024).…”
Section: Identification and Classification Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of other countries, a focus on either analysing the pattern of women director interlocks, or their value in inter-firm networks did not receive much attention in India, mainly on account of their marginal presence on company boards. Existing work on India is limited to exploratory analyses to determine the characteristics of social networks of Indian listed companies (Premsankar et al, 2015) 10 and examining the performance effect of committee interlocks on firm performance (Edacherian et al, 2023). None of these, however, factor in the gender of the director in their analyses.…”
Section: Women Director Interlocks In Indiamentioning
confidence: 99%